Chromosome aberrations in peripheral blood lymphocytes of lung cancer patients exposed to radon and air pollution. Issue 1 (January 2018) - Minina, Varvara I.; Sinitsky, Maxim Yu; Druzhinin, Vladimir G.; Fucic, Aleksandra; Bakanova, Marina L.; Ryzhkova, Anastasia V.; Savchenko, Yana A.; Timofeeva, Anna A.; Titov, Ruslan A.; Voronina, Elena N.; Volobaev, Valentin P.; Titov, Victor A.
Abstract : Lung cancer is one of the most common forms of cancer. The aim of this study was to validate chromosome aberrations in peripheral blood lymphocytes of lung cancer patients living in a region with high air pollution and increased background radon levels as a biomarker of cancer risk. A total of 417 lung cancer patients and 468 control participants were analysed using a chromosome aberration assay in peripheral blood lymphocytes. The results showed that chromatid-type aberrations (2.26±1.58 vs. 1.60±1.58) and chromosome-type aberrations (CSAs) (0.96±1.36 vs. 0.42±0.70) in lung cancer patients were increased significantly in comparison with the controls. The most significant two-fold increase was detected for CSAs (nonsmoking patients: 0.84±1.54 vs. 0.41±0.73%, smoking patients: 0.99±1.31 vs. 0.44±0.67%). The frequency of dicentric and ring chromosomes, double minutes and rogue cells was significantly higher ( P =0.002, 0.00002, 0.01, 0.0007) in the lung cancer patients. As both analysed groups lived in the same environment, our results show that increased radon levels were not the only source for the detected genome damage. Using binomial logistic regression, the estimated odds ratios and 95% confidence intervals adjusted for the main confounders (smoking, occupational exposure, age) were 1.31 (1.20–1.40) for chromatid-type aberrations, 1.28 (1.17–1.33), and 1.68 (1.49–1.88) for CSAs. It may be suggested that lung cancer patients show a significant increase in genome damage that may be caused by an interplay between exposure and individual low capacity of DNA repair, leading to genome instability.